Statistical parametric mapping analysis of muscle-oxygenation kinetics in response to repeated-sprint training in hypoxia - Hansen, C.; Brocherie, F.; Racinais, S.; Townsend, N.; Cocking, S.; Couderc, A.; Piscione, J.; Girard, O. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To examine the effect of repeated-sprint training in hypoxia (RSH) on oxygenation kinetics in the vastus lateralis muscle using statistical parametric mapping during repeated treadmill sprints in world-class female Rugby Sevens players.